2008
DOI: 10.1111/j.1365-3156.2007.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Access and barriers to measures targeted to prevent malaria in pregnancy in rural Kenya*

Abstract: Summaryobjectives To evaluate barriers preventing pregnant women from using insecticide-treated nets (ITN) and intermittent presumptive treatment (IPT) with sulphadoxine-pyrimethamine (SP) 5 years after the launch of the national malaria strategy promoting these measures in Kenya.methods All women aged 15-49 years were interviewed during a community survey in four districts between December 2006 and January 2007. Women pregnant in the last 12 months were asked about their age, parity, education, use of nets, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 25 publications
5
41
4
Order By: Relevance
“…We found that the time taken to reach health unit in hours was significant at determining ITN utilisation with those who reported to take more than an hour to reach health unit were 0.64 times less likely to utilise ITN than those who took an hour or less to reach health unit (P-value = 0.050). Similar result was obtained in a study by Gikandi et al where fewer women reported ITN use if they lived more than an hour walking distance to ante-natal clinic 23 . This could be because of lack of transport to the health unit or because of social responsibility in the home which can not make them free and they missed out ITN and vital health messages from the antenatal clinics, which could have influence over their attitude toward ITN utilisation.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…We found that the time taken to reach health unit in hours was significant at determining ITN utilisation with those who reported to take more than an hour to reach health unit were 0.64 times less likely to utilise ITN than those who took an hour or less to reach health unit (P-value = 0.050). Similar result was obtained in a study by Gikandi et al where fewer women reported ITN use if they lived more than an hour walking distance to ante-natal clinic 23 . This could be because of lack of transport to the health unit or because of social responsibility in the home which can not make them free and they missed out ITN and vital health messages from the antenatal clinics, which could have influence over their attitude toward ITN utilisation.…”
Section: Resultssupporting
confidence: 77%
“…This could be explained by the fact that those who initially had no ITN got it from health centre during ANC visit and was told the benefits of utilising ITN. A study by Gikandi et al in Kenya found that more than half of the net used by pregnant women were obtained from antenatal clinics 23 . Also, those who were having ITN were encouraged to utilise their ITN because of the benefits that they and their unborn baby will have if she utilise ITN.…”
Section: Resultsmentioning
confidence: 99%
“…The high number of those who attended secondary is not unconnected with Universal Basic Education (UBE) in Nigeria supported by UNICEF (UNICEF, 2002). Women with formal education were more likely to prevent malaria in pregnancy using ITN and IPT (Gikandi et al, 2008). Most of them were housewives as majority of them were wives of junior noncommissioned officer who are of the lower cadre of soldier of the Nigerian Army.…”
Section: Discussionmentioning
confidence: 99%
“…The wealth tertile was defined as 1) lowest tertile: soil and wood walls and terracotta roofs, only television sets or without any valuable electric items, only bikes or without any transport tools; 2) middle tertile: brick walls and terracotta roofs, television sets, motorcycles; 3) highest tertile: brick or reinforced concrete walls and roofs, television sets, and refrigerators, tractors or cars or trucks. [19][20][21][22] Statistical analysis. Data were double entered and cleaned in EpiData 3.1 (EpiData Association, Odense, Denmark), and analyzed in Epi Info 2000 (Centers for Disease Control and Prevention, Atlanta, GA).…”
Section: Methodsmentioning
confidence: 99%